Eksistensi Pelayanan Pemerintah Desa Studi Kasus Di Desa Mondatong Kecamatan Poigar Kabupaten Bolaang Mongondow - Christian Pangau; Ellys Rachman; Andi Yusuf Katili (Universitas Warmadewa, 2025)
Village government plays a strategic role in providing quality public services to the community, especially in realizing effective and responsive governance. However, in practice, there is still a gap between theory and implementation in the field, especially in Mondatong Village, Porigar District, Bolaang Mongondow Regency. Public services in this village have not run optimally, characterized by the maximum malfunction of the village office, limited human resources (HR) of village apparatus, and lack of service support facilities. This study aims to analyze the existence of Mondatong village government services by focusing on the organizational function of the village office, the quality and availability of human resources, and the completeness of service facilities. The method used is a descriptive qualitative approach, with data collection techniques in the form of observation, in-depth interviews, and documentation. The main findings of the study show that the existence of village government services has not been fully realized functionally; Village officials still lack competence, inadequate service facilities, and the community has not felt optimal public services. The results of this research are expected to be the basis for the village government in formulating a more effective service improvement strategy, as well as strengthening the application of public service principles as mandated in Law Number 25 of 2009 concerning Public Services.